Prediksi Kehilangan Hasil Jagung (Zea mays L.) Akibat Kompetisi Gulma Poaceae di Lahan Kering - Ngawit, I Ketut; Farida, Nihla; Azhari, Anjar Pranggawan (LPPM Universitas Mataram, 2024)
This research aims to determine the Poaceae weed species that have a significant effect on corn yield loss in dry land. The research method was descriptive and data collection using survey techniques in 10 sample plots measuring 1 m2 which were placed using random sampling. Observation parameters include the number of species and populations of weeds, the population of corn plants in plot-1 and the dry biomass weight of weeds and corn in plot-1. Quantitative data analysis by calculating relative density, relative frequency and relative dominance values ​​to calculate the importance value index and Summe Diminance Ratio (SDR). The results showed that the diversity, evenness, dominance and abundance of Poaceae weeds in corn plants in dry land was high. So it was found that seven species of weeds were dominant and continued to exist while the corn was growing, namely Paspalum vasginatum Sw., Leersia hexandra Sw., Digitaria longiflora (Retz.) Koel., Digitaria ciliaris (Retz.) Koel., Cynodon dactylon L., Eleusine indica Gaertn., and Panicum repens L. The competitiveness and ability to reduce corn yields of the weeds Paspalum vasginatum, Leersia hexandra and Digitaria longiflora are higher than other weeds, so that corn yield losses due to competition reach 16.45%, 7.48% and 4.40%. The weeds Brachiaria reptans, Axonopus compressus and Echinochloa colonum do not need to be controlled in corn after the plants are 45 DAT, because their competitiveness and ability to eliminate crop yields is very low.